3D model of frequency representation in the cochlear nucleus of the CBA/J mouse. Issue 7 (18th March 2013) - Muniak, Michael A.; Rivas, Alejandro; Montey, Karen L.; May, Bradford J.; Francis, Howard W.; Ryugo, David K.
Abstract The relationship between structure and function is an invaluable context with which to explore biological mechanisms of normal and dysfunctional hearing. The systematic and topographic representation of frequency originates at the cochlea, and is retained throughout much of the central auditory system. The cochlear nucleus (CN), which initiates all ascending auditory pathways, represents an essential link for understanding frequency organization. A model of the CN that maps frequency representation in 3D would facilitate investigations of possible frequency specializations and pathologic changes that disturb frequency organization. Toward this goal, we reconstructed in 3D the trajectories of labeled auditory nerve (AN) fibers following multiunit recordings and dye injections in the anteroventral CN of the CBA/J mouse. We observed that each injection produced a continuous sheet of labeled AN fibers. Individual cases were normalized to a template using 3D alignment procedures that revealed a systematic and tonotopic arrangement of AN fibers in each subdivision with a clear indication of isofrequency laminae. The combined dataset was used to mathematically derive a 3D quantitative map of frequency organization throughout the entire volume of the CN. This model, available online (http://3D.ryugolab.com/), can serve as a tool for quantitatively testing hypotheses concerning frequency and location in the CN. J. Comp. Neurol. 521:1510–1532, 2013. © 2012 Wiley Periodicals, Inc.